Detection of OXA-181/OXA-48 carbapenemase producing Enterobacteriaceae in Bangladesh - Khatun, Rehana; Shamsuzzaman, SM (Ibrahim Medical College Journal, 2016)
Carbapenem resistant Enterobacteriaceae (CRE) is becoming a major public health concern globally. Detection of carbapenem hydrolyzing enzyme carbapenemase in Enterobacteriaceae is important to institute appropriate therapy and to initiate preventive measures. This study was designed to determine the presence of carbapenemase producers among the CRE isolated from patients at Dhaka Medical College Hospital, Bangladesh. Twenty-nine CRE strains detected by disk diffusion technique were included in the study. Minimum inhibitory concentration of imipenem and tigecycline was determined by agar dilution method. Carbapenemase production was phenotypically detected by Modified Hodge test while MBL producers were detected by combined disk and double disk synergy tests. Genes encoding blaNDM-1, blaOXA-181, blaOXA-48, blaKPC, blaCTX-M-15, blaOXA-1-group were identified by polymerase chain reaction (PCR). Out of 29 CRE, nineteen (65.6%) were positive for carbapenemase by any of the three phenotypic tests namely MHT, CD or DD tests. Those 19 isolates were also positive either for blaNDM-1 or blaOXA-181/blaOXA-48 by PCR. Of the 19 PCR positive isolates, the rate of positivity for blaNDM- 1, blaOXA-181/blaOXA-48 and blaNDM-1+ blaOXA-181/blaOXA-48 was 73.7% (14/19), 57.9% (11/19) and 31.6% (6/19) respectively. Both blaOXA-181 and blaOXA-48 co-existed. All the carbapenemase producing organisms harboured blaCTX-M-15 except one C. freundii strain. The rate of resistance to different classes of antibiotics ranged from 63.2% to 100% except colistin and tigecycline. Organisms positive for OXA-181/OXA-48 had a low level of resistance to carbapenem (MIC 1 - 4 ì g/ml) while with NDM-1 had high level resistance to imipenem (MICs 16 - ? 32 ì g/ ml). Out of 19 carbapenemase positive isolates, 12 (63.16%) were extensively drug-resistant (XDR) and were only sensitive to tigecycline and colistin. The result of this study showed the presence of blaOXA-181/ blaOXA-48, blaNDM-1 positive strains in Bangladesh and colistin and tigecycline were the most effective drugs against carbapenemase producing Enterobacteriaceae (CPE). Epidemiological monitoring of carbapenemase producing organisms in Bangladesh is important to prevent their dissemination. Ibrahim Med. Coll. J. 2015; 9(2): 45-51